2018
DOI: 10.1016/j.newast.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Formation and spatial distribution of hypervelocity stars in AGN outflows

Abstract: We study star formation within outflows driven by active galactic nuclei (AGN) as a new source of hypervelocity stars (HVSs). Recent observations revealed active star formation inside a galactic outflow at a rate of ∼ 15 M ⊙ yr −1 . We verify that the shells swept up by an AGN outflow are capable of cooling and fragmentation into cold clumps embedded in a hot tenuous gas via thermal instabilities. We show that cold clumps of ∼ 10 3 M ⊙ are formed within ∼ 10 5 yrs. As a result, stars are produced along outflow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The prominent CN line wings of Mrk 231 may indicate that the outflow is bathed in a strong UV radiation field, either due to star formation in the galaxy disk or to new stars forming within the outflow itself. The latter is a scenario proposed by various recent models and simulations (Zubovas et al 2013;Zubovas & King 2014;Ishibashi & Fabian 2012;Ishibashi et al 2013;El-Badry et al 2016;Wang & Loeb 2018;Decataldo et al 2019). Star formation in the outflow could have major implications, since such stars would have highly radial orbit and could, for instance, contribute to the formation of…”
Section: Enhanced Cn/hcn Abundance Ratiosmentioning
confidence: 94%
“…The prominent CN line wings of Mrk 231 may indicate that the outflow is bathed in a strong UV radiation field, either due to star formation in the galaxy disk or to new stars forming within the outflow itself. The latter is a scenario proposed by various recent models and simulations (Zubovas et al 2013;Zubovas & King 2014;Ishibashi & Fabian 2012;Ishibashi et al 2013;El-Badry et al 2016;Wang & Loeb 2018;Decataldo et al 2019). Star formation in the outflow could have major implications, since such stars would have highly radial orbit and could, for instance, contribute to the formation of…”
Section: Enhanced Cn/hcn Abundance Ratiosmentioning
confidence: 94%
“…Ishibashi et al (2013) have even suggested that star formation in AGN-driven outflows can contribute to the observed size evolution of ellitpical galaxies across the cosmic epochs. Wang & Loeb (2018) have also suggested that the double-shells often observed in elliptical galaxies, typically ascribed to merging events, can actually be the result of star formation in outflows.…”
Section: Formation Of the Spheroidal Component Of Galaxiesmentioning
confidence: 99%
“…Within this context star formation in outflows has also been invoked to explain the population of Hypervelocity stars in the Galactic halo (Wang & Loeb 2018;Silk & Mamon 2012;Zubovas et al 2013c).…”
Section: Formation Of the Spheroidal Component Of Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we follow the prescription of our previously derived model for star formation within shells (Wang & Loeb 2018). The swept-up gas cools and fragments into cold clumps embedded in a hot tenuous gas via a thermal instability, which occurs if the heating rate at a constant pressure rises faster than the cooling rate as a function of temperature, consistent with observations (Maiolino et al 2017) and numerical simulations (Ferrara & Scannapieco 2016;Schneider et al 2018).…”
Section: Star Formationmentioning
confidence: 55%